De Novo Transcriptome Assembly, Gene Annotations, and Characterization of Functional Profiling Reveal Key Genes for Lead Alleviation in the Pb Hyperaccumulator Greek Mustard (Hirschfeldia incana L.) - Said El Hasnaoui; Mouna Fahr; Mohamed Zouine; Abdelaziz Smouni (Current Issues in Molecular Biology, 2022)
Lead (Pb) contamination is a widespread environmental problem due to its toxicity to living organisms. Hirschfeldia incana L., a member of the Brassicaceae family, commonly found in the Mediterranean regions, is characterized by its ability to tolerate and accumulate Pb in soils and hydroponic cultures. This plant has been reported as an excellent model to assess the response of plants to Pb. However, the lack of genomic data for H. incana hinders research at the molecular level. In the present study, we carried out RNA deep transcriptome sequencing (RNA-seq) of H. incana under two conditions, control without Pb(NO3)2 and treatment with 100 µM of Pb(NO3)2 for 15 days. A total of 797.83 million reads were generated using Illumina sequencing technology. We assembled 77,491 transcript sequences with an average length of 959 bp and N50 of 1330 bp. Sequence similarity analyses and annotation of these transcripts were performed against the Arabidopsis thaliana nr protein database, Gene Ontology (GO), and KEGG databases. As a result, 13,046 GO terms and 138 KEGG maps were created. Under Pb stress, 577 and 270 genes were differentially expressed in roots and aboveground parts, respectively. Detailed elucidation of regulation of metal transporters, transcription factors (TFs), and plant hormone genes described the role of actors that allow the plant to fine-tune Pb stress responses. Our study revealed that several genes related to jasmonic acid biosynthesis and alpha-linoleic acid were upregulated, suggesting these components’ implication in Hirschfeldia incana L responses to Pb stress. This study provides data for further genomic analyses of the biological and molecular mechanisms leading to Pb tolerance and accumulation in Hirschfeldia incana L.